The Impact of Trade War on Fiscal Revenue Through Trade Taxes in 5 Asian Countries - Salsabila, Adin; Azwardi, Azwardi; Sukanto, Sukanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The trade war between the United States and China, which began in 2018, has triggered shifts in trade flows and the relocation of investments to various Asian countries. These developments have the potential to affect fiscal revenue through changes in international trade tax revenue. This study aims to analyze the effects of imports, Gross Domestic Product (GDP), exchange rates, and the trade war on international trade tax revenue in five Asian countries during the period 2010–2023. This study employs panel data regression using the Fixed Effects Model (FEM). The results indicate that imports and exchange rates have a positive and significant effect on international trade tax revenue. Conversely, GDP has a negative effect, suggesting a shift in the government’s revenue sources from trade taxes toward domestic taxes as the economy grows. The trade war dummy variable also has a positive and significant effect, indicating that the U.S.–China trade war increased international trade tax revenue in several Asian countries through the diversion of trade flows and the relocation of economic activities. These findings suggest that global trade dynamics play an important role in shaping a country’s fiscal revenue.